Prinsip-prinsip Metode Dakwah menurut Al-Qurâan - Aliyudin, Aliyudin (Jurnal Ilmu Dakwah, 2010)
The method of dawah is one element of dawah process that has important and strategic role for the success of dawah acitivies. Methods of dawah has increase constantly in line with the situation and the condition of its scope. However, the Koran laid the foundation of standardized with respect to the principles that must be built in a variety of methods of propaganda. This principle in which contained in the Quran al-Nahl verse 125 : al-Hikmah (wisdom) al-mauidzah al-hasanah (good examplary), and al-Mujadalah al-ahsan (debate with the best way), then actualized and reinforced with the principles of dawah performed by Prophet Muhammad (peace be upon him).